(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
The study aimed to elaborate the speech acts used and the difficulties occurred when performing speech acts by the fourth semester of English department students at Letters Faculty of Indonesia Moslem University. The writer used a qualitative research as the research method. The writer collected data by verbal test to analyze this study. The results of this study indicated that the speech acts used by the fourth semester of English Department students at Letters Faculty of Indonesia Moslem University mostly was Locutionary as it was the most common type of speech acts used in communication. In addition, regarding the difficulties occurred in performing speech acts by the students, was how the students needed to change the literal meaning of the sentence to the intended meaning because it sometimes confused the speaker and the listener to understand each other.